2003
DOI: 10.2320/matertrans.44.2020
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Low Coercivity of Fe-(Al, Ga)-(P, C, B, Si, Ge) Bulk Glassy Alloys

Abstract: The magnetic properties of the glassy Fe-(Al, Ga)-(P, C, B, Si, Ge) alloys have been compared with those of the conventional Fe-based amorphous alloys to clarify the feature of the glassy alloys as a soft magnetic material. The glassy Fe-(Al, Ga)-(P, C, B, Si, Ge) alloys exhibit lower saturation magnetization (J s ) than that of the conventional Fe-(B, Si, C) amorphous alloys with the same Fe content. The glassy alloys also have larger saturation magnetostriction constant ( s ) than that of the conventional Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(27 citation statements)
references
References 54 publications
(87 reference statements)
1
25
0
1
Order By: Relevance
“…Taking account of the difference in the optimum annealing temperature for H c , 748 K for the glassy alloy and 653 K for the amorphous alloy, we can see that the Fe 76 Si 9 B 10 P 5 glassy alloy exhibits the higher thermal stability of magnetic softness, which should indicate the higher stability of the glassy phase than the amorphous phase. 11,12) Figure 4 shows the compressive stress-strain curve (a), and SEM micrographs revealing the compressive fracture surface (b) and shear bands on the specimen surface (c) of the Fe 76 Si 9 B 10 P 5 BMG with a diameter of 1.5 mm, respectively. It can be seen that the specimen shows an initial elastic deformation behavior with an elastic strain of 1.9%, then begins to yield at about 3.3 GPa, followed by some plastic deformation of 0.7% before fracture.…”
Section: Resultsmentioning
confidence: 99%
“…Taking account of the difference in the optimum annealing temperature for H c , 748 K for the glassy alloy and 653 K for the amorphous alloy, we can see that the Fe 76 Si 9 B 10 P 5 glassy alloy exhibits the higher thermal stability of magnetic softness, which should indicate the higher stability of the glassy phase than the amorphous phase. 11,12) Figure 4 shows the compressive stress-strain curve (a), and SEM micrographs revealing the compressive fracture surface (b) and shear bands on the specimen surface (c) of the Fe 76 Si 9 B 10 P 5 BMG with a diameter of 1.5 mm, respectively. It can be seen that the specimen shows an initial elastic deformation behavior with an elastic strain of 1.9%, then begins to yield at about 3.3 GPa, followed by some plastic deformation of 0.7% before fracture.…”
Section: Resultsmentioning
confidence: 99%
“…We examined in more details the contribution of internal stress to coercivity. It has previously been reported that the coercivity is proportional to the ratio of saturation magnetostriction ( s ) to saturation magnetization 27) and hence the slope is related to the volume and density of internal defects considering mainly of free volumes in the glassy structure. Figure 8 shows good linear relations between H c and the ratio of s to J s for Fe-based glassy and amorphous alloys.…”
Section: Features Of Alloy Components In Late Transitionmentioning
confidence: 99%
“…The coercivities are very small and also comparable. It is known that the coercivity strongly depends on the structure of the sample [21,22]; so it is possible to say that the M.A. and (M.A.)…”
Section: Invited Articlementioning
confidence: 99%